2017
DOI: 10.1093/nar/gkx1016
|View full text |Cite
|
Sign up to set email alerts
|

mVOC 2.0: a database of microbial volatiles

Abstract: Metabolic capabilities of microorganisms include the production of secondary metabolites (e.g. antibiotics). The analysis of microbial volatile organic compounds (mVOCs) is an emerging research field with huge impact on medical, agricultural and biotechnical applied and basic science. The mVOC database (v1) has grown with microbiome research and integrated species information with data on emitted volatiles. Here, we present the mVOC 2.0 database with about 2000 compounds from almost 1000 species and new featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
248
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(256 citation statements)
references
References 22 publications
0
248
0
8
Order By: Relevance
“…However, other BVCs produced by bacteria protect plants from biotic stress, and previous work demonstrated that B. subtilis strains produce a number of them (Fiddaman and Rossal, 1993; Chaurasia et al, 2005; Farrag et al, 2006; Arrebola et al, 2010). B. simplex and B. subtilis are known to synthesize 2-propanone, phenol, 1-decanol, 2-undecanone, 1-decanol, 1-dodecanol, methyl-tetradecanoate, and 2-ethyl-3,5-dimethylpyrazine, and many other microbial VOCs (Velivelli et al, 2015; Lemfack et al, 2018). Gu et al, 2007 found that B. simplex BVCs from six distinct isolates killed almost 100% of the parasitic nematodes Panagrellus redivivus and Bursaphelenchus xylophilus .…”
Section: Discussionmentioning
confidence: 99%
“…However, other BVCs produced by bacteria protect plants from biotic stress, and previous work demonstrated that B. subtilis strains produce a number of them (Fiddaman and Rossal, 1993; Chaurasia et al, 2005; Farrag et al, 2006; Arrebola et al, 2010). B. simplex and B. subtilis are known to synthesize 2-propanone, phenol, 1-decanol, 2-undecanone, 1-decanol, 1-dodecanol, methyl-tetradecanoate, and 2-ethyl-3,5-dimethylpyrazine, and many other microbial VOCs (Velivelli et al, 2015; Lemfack et al, 2018). Gu et al, 2007 found that B. simplex BVCs from six distinct isolates killed almost 100% of the parasitic nematodes Panagrellus redivivus and Bursaphelenchus xylophilus .…”
Section: Discussionmentioning
confidence: 99%
“…, Lemfack et al. ). Ketones undoubtedly belong to biologically active compounds, since they are able to participate in many chemical interactions (Forney and Markovetz ).…”
mentioning
confidence: 99%
“…The first microbial volatile database “mVOC” is available now (Lemfack et al. ). Bacterial VOCs are considered sensitive and specific biomarkers for bacterial detection in human specimens (Sohrabi et al.…”
mentioning
confidence: 99%
“…Our data highlight that soil microbes were strongly associated with soil's volatilome. Bacteria and fungi are well known emitters of volatile compounds (Lemfack et al ., ), and we have speculated earlier based on undescribed (and mostly uncultivable) microbial taxa that soil might contain a huge diversity of undescribed volatiles (Schenkel et al ., ). This hypothesis is corroborated here by the fact that most volatiles of the present study could not be identified.…”
Section: Discussionmentioning
confidence: 94%